Sexual function in Chinese women with different clinical phenotypes of polycystic ovary syndrome - Xuanxuan Tian; Xiangyan Ruan; Juan Du; Jiaojiao Cheng; Rui Ju; Alfred O. Mueck (Taylor & Francis Group, 2023)
Objective: To investigate sexual function stratified according to four clinical phenotypes of polycystic ovary syndrome (PCOS) and its association with clinical and quality of life parameters, and to compare these with healthy controls in Chinese women with PCOS. Methods: A cross-sectional study was designed in 1000 PCOS women and 500 control women aged 18-45 years. PCOS women were grouped into four clinical phenotypes according to the Rotterdam Criteria. FSFI (Female Sexual Function Index), SF-12 (the 12-item short form health survey) and clinical and hormonal characteristics likely to affect sexual function were determined. Results: 809 PCOS women and 385 control women with complete parameters were evaluated after screening. Phenotype A had a lower total FSFI mean score (23.14 ± 3.22) compared with phenotype D and control group (p < 0.05). The control group had the highest total FSFI mean score (24.98 ± 3.78). For the percentage at risk of sexual dysfunction, phenotype A (87.5%) and phenotype B (82.46%) had a higher risk of female sexual dysfunction (FSD) than that in phenotype C (75.34%), phenotype D (70.56%) and control group (61.30%) (p < 0.05). SF-12 mental domain scores were significantly lower in phenotypes A and B compared with phenotypes C and control group (p < 0.05). Infertility treatment, bioavailable testosterone, psychological factors, age and waist circumference presented negative correlation with female sexual function. Conclusions: The risk of FSD in PCOS women seemed to be associated with PCOS clinical phenotypes. The classical PCOS phenotype with oligo-ovulation and hyperandrogenism had a higher risk of sexual dysfunction.